Little Fanny's journal, or, My own child's book - Tytler, Margaret Fraser (Preservation and Access for American and British Children's Literature, 1850-1869 (NEH PA-23536-00), 1851)
Written by an adult in the form of a diary of a child whose parents have gone away for a month and she is trying not to be anxious and sad.